Motor learning through virtual reality in elderly - a systematic review - Ribeiro-Papa,Denise Cardoso (2016)
INTRODUCTION: Decline in physical function is a common feature of older age and has important outcomes in terms of physical health as it relates to quality of life. Our capacity for motor learning allows us to flexibly adapt movements to an ever-changing environment. The term Virtual Reality refers to a wide variety of methods used to simulate an alternative or virtual world. OBJECTIVE: To analyze the results shown in previous studies on motor learning with Virtual Reality use in elderly participants. METHOD: To select the articles, three steps were followed. A systematic literature review was performed without time limitation. The research was carried out using PubMed, BVS and Web of science; considering the keywords, we included articles that showed the following three terms: elderly, virtual reality and motor learning. RESULTS: The initial search yielded 49 articles. After duplicates were removed, two of the authors independently evaluated the title and abstract of each article against the study inclusion criteria. From these, 45 articles were excluded based on title and abstract. Finally, four articles met the inclusion criteria. CONCLUSION: Although few studies were conducted on motor learning in elderly people through virtual reality and, even fewer were of good quality, it was shown that elderly people, with or without a specific disease, can benefit from interventions based on virtual reality to improve motor learning skills.